1987
DOI: 10.1002/pros.2990100111
|View full text |Cite
|
Sign up to set email alerts
|

Medical, life‐style, and occupational risk factors for prostate cancer

Abstract: Information on suspected risk factors for prostate cancer was obtained from in-person interviews as part of a case-control study of tissue sex hormone receptors and serum hormone levels. The risk factors examined were medical history (including venereal disease), sexual history, smoking, alcohol consumption, and occupational exposures. Study subjects were 40 prostate cancer patients and 64 benign prostatic hyperplasia controls who were newly diagnosed during 1984-1985 at North Carolina Memorial Hospital in Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
3
7

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 18 publications
3
71
3
7
Order By: Relevance
“…Moreover, in an epidemiological study comparing npg the X-ray evidence of prostatic calculi with self-report of a history of prostatic calculi, the authors found no relationship between the presence of prostatic calculi and PCa [24,25]. Of note, there is a large difference in the detection rate of prostatic calculi using X-rays and that using ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in an epidemiological study comparing npg the X-ray evidence of prostatic calculi with self-report of a history of prostatic calculi, the authors found no relationship between the presence of prostatic calculi and PCa [24,25]. Of note, there is a large difference in the detection rate of prostatic calculi using X-rays and that using ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were excluded if they did not provide enough data to allow calculation of relative risks (RRs) with 95% confidence intervals (CI). Besides, publications were excluded if the exposure was metabolic syndrome (Laukkanen et al, 2004) or hyperglycemia (Grundmark et al, 2010), or controls were men with benign prostatic hyperplasia (Checkoway et al, 1987;Rosenberg et al, 2002), or the outcome was PCa mortality (Coughlin et al, 1996, Will et al, 1999 or recurrence (Chan et al, 2005). Additionally, publications were excluded if they were designed to clarify the association between DM and severity of PCa among patients having radical prostatectomy (Abdollah et al, 2011), or radiation therapy (Mitin et al, 2011), or having a prostate biopsy (Moreira et al, 2011) due to elevated PSA level.…”
Section: Selection Of Published Studiesmentioning
confidence: 99%
“…As listed in Table 1, our systematic literature search We excluded 5 articles (Checkoway et al, 1987;Smith et al, 1992;La Vecchia et al, 1994;Coughlin et al, 1996;Rosenberg et al, 2002) articles included in the two previous meta-analyses. The two articles by Checkoway et al (Checkoway et al, 1987) and Rosenberg et al (Rosenberg et al, 2002) were excluded because the controls were men with benign prostatic hyperplasia (BPH).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations